Rubiscolins - Highly Potent Peptides Derived from Plant Proteins - Perlikowska, Renata; Janecka, Anna (Mini Reviews in Medicinal Chemistry, 2018)
Rubiscolins are two naturally occurring, linear peptides, isolated from the pepsin digests of D-ribulose-1,5-bisphosphate carboxylase/oxygenase (RuBisCo) from spinach leaves. Their sequences are as follows: Tyr-Pro-Leu-Asp-Leu (YPLDL, rubiscolin-5) and Tyr-Pro-Leu-Asp-Leu-Phe (YPLDLF, rubiscolin-6, also known as rubixyl). Though their structure does not resemble typical opioid peptides, rubiscolins were found to exhibit high affinity and selectivity for the delta opioid receptor and an antinociceptive effect in mice after oral administration. Moreover, orally administered rubiscolin-6 was shown to possess orexigenic, anxiolytic-like, and memory-enhancing activities in mice. This review summarizes various biological activities of rubiscolins in mammalian organism and recent developments on the structure-activity relationship of rubiscolin analogs, aimed at improving their pharmacological properties. Naturally occurring substances, such as rubiscolins, may provide a rational and powerful approach in the design of new therapeutics or functional foods.
Keywords: opioid peptides